Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Terbuka di Provinsi Banten Tahun 2020-2023 - dwi lestari, indri; Sulistiyaningsih, Nur Ayu; Sibatuara, Trisha Clarita; Nilasari, Aprillia; Arisetyawan, Kukuh (Universitas Negeri Surabaya, 2024)
This study investigates the impact of Labor Force Participation Rate, Minimum Wage, and Population Size on the Open Unemployment Rate across Districts/Cities in Banten Province. The research employs panel data, incorporating both cross-sectional and time series data from 2020-2023. Through the application of Fixed Effect Model (FEM), the findings reveal that Labor Force Participation Rate and Population Size demonstrate no significant effect, whereas Minimum Wage exhibits a significant influence on the Unemployment Rate in Banten. The simultaneous test indicates that these three variables collectively have a significant impact on unemployment levels in Banten Province.